2010
DOI: 10.1038/oby.2010.59
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Subcutaneous and Visceral Adipose Tissue and Insulin Resistance in the Framingham Heart Study

Abstract: Insulin resistance is associated with central obesity and an increased risk of cardiovascular disease. Our objective is to examine the association between abdominal subcutaneous (SAT) and visceral adipose tissue (VAT) and insulin resistance, to determine which fat depot is a stronger correlate of insulin resistance, and to assess whether there was an interaction between SAT, VAT, and age, sex, or BMI. Participants without diabetes from the Framingham Heart Study (FHS), who underwent multidetector computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
269
1
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(295 citation statements)
references
References 34 publications
8
269
1
10
Order By: Relevance
“…Thus, it is not surprising that VAT more so than SAT was positively associated with a constellation of metabolic variables characteristic of the metabolic syndrome and CVD risk. Although SAT does have some of the same metabolic effects as VAT, it is not as strongly correlated with proinflammatory, hyperinsulinemic markers (29,30). Of the metabolic variables examined, SAT had a significant relationship with SBP only.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, it is not surprising that VAT more so than SAT was positively associated with a constellation of metabolic variables characteristic of the metabolic syndrome and CVD risk. Although SAT does have some of the same metabolic effects as VAT, it is not as strongly correlated with proinflammatory, hyperinsulinemic markers (29,30). Of the metabolic variables examined, SAT had a significant relationship with SBP only.…”
Section: Discussionmentioning
confidence: 92%
“…Also, this study was carried out in men only. Nevertheless, studies have shown similar (bivariate) associations between VAT, SAT, IHL, and MVR and insulin resistance in women, as well as improvements in these variables with weight loss (2,(25)(26)(27)(28). Amounts of IHL and VAT are, however, typically greater in men, whereas the amount of SAT is greater in women (2, 10); this might affect the relative contribution of each mediator in women in the multiple mediator models.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 90%
“…SAT's effect on insulin resistance is controversial; the increased lipolysis and adipokine dysregulation in SAT is considered to contribute to insulin resistance (2), yet a fat distribution pattern with high SAT and low VAT volumes is considered a metabolically healthy phenotype (7). The involvement of IHL, on the other hand, is also debated, as IHL has been postulated to be both a cause and a consequence of insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the reduction in the amount of VAT is of great importance, since the accumulation of adipose tissue in this compartment is more strongly associated with insulin resistance and type 2 diabetes compared with SAT (Bray et al 2008, Preis et al 2010. The reasons for this are multiple.…”
Section: Discussionmentioning
confidence: 99%